Jadomycins: A potential chemotherapy for multi‐drug resistant metastatic breast cancer - Esther P. Bonitto; Brendan T. McKeown; Kerry B. Goralski (Wiley, 2021)
Abstract Breast cancer causes the most cancer fatalities in women worldwide. Approximately one‐third of breast cancers metastasize, or spread from primary tumors to other tissues, and have a 70% 5‐year mortality rate. Current breast cancer treatments like doxorubicin and paclitaxel become ineffective when breast cancer cells develop multi‐drug resistance and overexpress ATP‐binding cassette transporters, as the transporters cause a substantial efflux of the chemotherapies. Jadomycins, a group of molecules isolated from Streptomyces venezuelae ISP5230, are shown to be cytotoxic against a variety of cancers, especially breast cancer. Furthermore, jadomycins retain their cytotoxic properties in multi‐drug resistant breast cancer cells, as they are not expelled through ATP‐binding cassette transporters. Here, we describe the research that supports the potential use of jadomycins as a novel chemotherapy in the treatment of multi‐drug resistant, metastatic breast cancer. We present the supportive findings, as well as the mechanisms of action investigated thus far. These include copper‐mediated reactive oxygen species generation, aurora B kinase inhibition, and topoisomerase IIα and IIβ inhibition. We also suggest future directions of jadomycin research, which will help to determine if jadomycins can be used as a breast cancer chemotherapy in clinical practice.